Analisis Pengelolaan Keuangan Desa Balee Ujong Rimba Pada Kantor Camat Mutiara Timur Kabupaten Pidie - Zulkifli Umar; Irmawati; Nadia Zakia (Asosiasi Dosen dan Praktisi Ekonomi Nusantara, 2025)
This research was conducted at the East Mutiara Sub-district Office, Pidie Regency with the aim of finding out the analysis of financial management of Balee Ujong Rimba Village at the East Mutiara Sub-district Office, Pidie Regency in 2016. The formulation of the problem in this study is how to analyze the financial management of Balee Ujong Rimba Village at the East Mutiara Sub-district Office, Pidie Regency. This study uses a qualitative descriptive method, namely presenting research findings based on the theoretical foundations that have been put forward in the literature review. The method of data collection is through direct interviews, observations and documentation related to the financial management of Balee Ujong Rimba Village. The results of this study show that Balee Ujong Rimba Village has not fully implemented the rules in managing village finances based on Permendagri No. 113 of 2014. In the implementation of village financial management, village officials have not fully understood the guidelines in Permendagri No. 113 of 2014 which requires villages in financial management to be carried out in a transparent, accountable and computerized manner.